The Relationship Between Knowledge of Food Additives and The Attitudes of UNP Culinary Studenst in Concuming Foods That Contain Flavorings, Colorins, and Presertatives - Turrahmi, Vadhila; Faridah, Anni (Universitas Negeri Padang, 2023)
This research is motivated by technological advances that produce food using food additives to improve quality. The problem arises because there are people who use food additives beyond the limit. The purpose of this research is to describe: 1) the level of knowledge of food additives, 2) attitudes of students in consuming foods, 3) analyze the relationship betweet konwledge of food additives with students’ attitudes in consuming foods. This type of research uses quantitative methods, correlation approaches. The population in this study were culinary students from class of 2019 and 2020. The research sample is 77 people selected by propotional random sampling. Data was collected by distributing questionnaires via google form. Research results show: 1) the level of students’ knowledge about food additives is in the medium category with a percentage 48%, 2) the level of attitudes towards consuming food is in the medium category with a percentage of 32%, 3) there is a positive and significant relationship between knowledge off food additives and the attitude of consuming food with a correlation value of rxy 0,366 and Tcount (3.404) > Ttable (1.991). This means that the higher the knowledge, the higher the attitude of students in consuming food and vice versa.